2022
DOI: 10.1002/ped4.12325
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targeted therapies for pediatric atypical teratoid/rhabdoid tumors

Abstract: Atypical teratoid/rhabdoid tumors (AT/RTs) are lethal central nervous system tumors, which are primarily diagnosed in infants. Current treatments for AT/RTs include surgery, radiotherapy, and chemotherapy; these treatments have poor prognoses and challenging side effects. The pivotal genetic event in AT/RT pathogenesis comprises the inactivation of SMARCB1 or SMARCA4. Recent epigenetic studies have demonstrated mutual and subtype-specific epigenetic derangements that drive tumorigenesis; the exploitation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…There is an increased emphasis on studies to assess the effectiveness of molecularly targeted therapies for AT/RTs. AT/RTs are thought to result from chromatin remodeling due to the inactivation of SMARCB1 or SMARCA4 , histone modification due to reduced regulation of H3K27, and DNA methylation due to dysregulation of Notch/sonic hedgehog (ATRT-SHH), tyrosinase enzyme (ATRT-TYR), and the MYC oncogene (ATRT-MYC) [ 21 , 23 ]. Inhibitors used in targeted therapy clinical trials to treat AT/RT include mTOR (drug: Sirolimus), EZH2 (drug: Tazemetostat), and CDK4/6 (drug: Ribociclib) [ 24–26 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased emphasis on studies to assess the effectiveness of molecularly targeted therapies for AT/RTs. AT/RTs are thought to result from chromatin remodeling due to the inactivation of SMARCB1 or SMARCA4 , histone modification due to reduced regulation of H3K27, and DNA methylation due to dysregulation of Notch/sonic hedgehog (ATRT-SHH), tyrosinase enzyme (ATRT-TYR), and the MYC oncogene (ATRT-MYC) [ 21 , 23 ]. Inhibitors used in targeted therapy clinical trials to treat AT/RT include mTOR (drug: Sirolimus), EZH2 (drug: Tazemetostat), and CDK4/6 (drug: Ribociclib) [ 24–26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several chemotherapeutic regimens have been described for the treatment of ATRT, including the modified Intergroup Rhabdomyosarcoma III protocol, St. Jude medulloblastoma protocol, malignant rhabdoid tumor protocol and more [11,13,[35][36][37][38]. The majority of chemotherapy agents in these protocols include vincristine, cyclophosphamide, cisplatin, and etoposide.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Recent studies have suggested that these subgroup-specific epigenetic and transcriptomic profiles may be utilized to identify therapeutic vulnerabilities and provide targeted treatment that may improve current clinical outcomes [ 141 ]. Some of these novel molecular therapies for ATRT are discussed in the following section.…”
Section: Advances In Molecular Subgrouping Of Atrtmentioning
confidence: 99%